Graphite tailing lightweight thermal insulation building material and preparation method thereof

Through nano foaming agent mechanical foaming technology, graphite tailings are developed into foam concrete, which solves the problem of limited application of graphite tailings in building materials, and achieves a large number of green, efficient and high-quality absorption of graphite tailings, and produces building materials with excellent insulation properties and good fire resistance.

CN119822866APending Publication Date: 2025-04-15SHENZHEN KEYU ENVIRONMENTAL PROTECTION IND CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510157754.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Graphite tailings are limited in the application of building materials, and traditional processing technology cannot effectively utilize it, resulting in uncertain product quality and high energy consumption.

Method used

Nano foaming agent is used for mechanical foaming to prepare high-performance lightweight thermal insulation building materials, and graphite tailings are developed into foam concrete through physical foaming technology to avoid high-temperature sintering and reduce energy consumption.

Benefits of technology

It has achieved a large, green, efficient and high-quality absorption of graphite tailings, and produced building materials with low density, high strength, excellent thermal insulation performance and good fire resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822866A_ABST
    Figure CN119822866A_ABST
Patent Text Reader

Abstract

The invention provides a graphite tailing lightweight thermal insulation building material and a preparation method thereof, and relates to the technical field of waste resource utilization. The preparation method comprises the following steps: mechanically foaming a nano foaming agent to obtain prefabricated foam; mixing the graphite tailing powder, cement, water and a water reducing agent to obtain a mixture; mixing the mixture with prefabricated foam to obtain concrete foam; the concrete foam is subjected to mold forming and curing maintenance in sequence, and the graphite tailing light heat preservation building material is obtained. Graphite tailings cannot be effectively contained in building materials in a traditional processing technology, especially in building materials needing high strength and high stability, a physical foaming technology is adopted, the graphite tailings are developed into the high-performance light-weight heat-preservation building materials, and the heat-preservation performance of the building materials is improved. The obtained lightweight thermal insulation building material has excellent thermal insulation performance, low density, high strength and good fire resistance. According to the method, large-amount, green, efficient and high-quality consumption of the graphite tailings is realized, and the method is low in energy consumption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of waste resource utilization, and in particular to a graphite tailings lightweight thermal insulation building material and a preparation method thereof. Background Art

[0002] Graphite tailings are waste or residues generated during the mining and processing of graphite. These tailings are mainly the ore parts that have not been effectively extracted after beneficiation, crushing, flotation and other processes. At present, the comprehensive utilization and environmental governance of graphite tailings have become an important direction for the development of the graphite industry. Improper treatment of graphite tailings will cause serious pollution to the surrounding environment. At present, the main treatment method of graphite tailings in the civil engineering field is to prepare sintered bricks. The preparation of sintered bricks requires high-temperature sintering and high energy consumption. Summary of the invention

[0003] In view of this, the purpose of the present invention is to provide a graphite tailings lightweight thermal insulation building material and a preparation method thereof. The present invention prepares graphite tailings into high-performance lightweight thermal insulation building materials through foaming technology, without high-temperature sintering and low energy consumption.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The present invention provides a method for preparing a lightweight thermal insulation building material of graphite tailings, comprising the following steps:

[0006] Mechanically foaming a nano foaming agent to obtain prefabricated foam; the nano foaming agent comprises the following components in percentage by weight: 0.1-1% alkyl glycoside, 0.1-1% nano bentonite, 0.05-1% cellulose reinforcing agent, and the balance water;

[0007] Mixing graphite tailings powder, cement, water and a water reducing agent to obtain a mixture;

[0008] mixing the mixed material with prefabricated foam to obtain concrete foam;

[0009] The concrete foam is sequentially molded and cured to obtain the graphite tailings lightweight thermal insulation building material.

[0010] Preferably, the air pressure of the mechanical foaming is 0.3-3 MPa, and the density of the prefabricated foam is 35-70 g / L.

[0011] Preferably, the particle size of the graphite tailings powder is 160-200 mesh; and the cement is PO 42.5 cement.

[0012] Preferably, the mass ratio of the graphite tailing powder to cement is 7:3-3:7, the mass ratio of the water to the total mass of cement and graphite tailing powder is 0.2:1, and the mass of the water reducer is 0.1-0.3% of the total mass of graphite tailing powder and cement.

[0013] Preferably, the mass of the nano foaming agent in the prefabricated foam is 6-16% of the total mass of the graphite tailing powder and cement in the mixture.

[0014] Preferably, the mixing of the mixed material and the prefabricated foam is carried out under stirring, and the stirring rate is 10 r / min.

[0015] Preferably, the mold forming includes mold installation and pre-curing, and the mold is removed after the pre-curing; the pre-curing is natural curing, and the time of the natural curing is 0.5 to 2 days.

[0016] Preferably, the curing is standard curing, and the time of the standard curing is 25 to 28 days.

[0017] The present invention provides a graphite tailings lightweight thermal insulation building material prepared by the preparation method described in the above technical solution.

[0018] Preferably, the graphite tailings lightweight thermal insulation building material comprises building blocks or thermal insulation wall panels.

[0019] The present invention provides a method for preparing a graphite tailings lightweight thermal insulation building material, comprising the following steps: mechanically foaming a nano foaming agent to obtain a prefabricated foam; mixing graphite tailings powder, cement, water and a water reducer to obtain a mixture; mixing the mixture with the prefabricated foam to obtain a concrete foam; and sequentially performing mold forming and curing and curing on the concrete foam to obtain the graphite tailings lightweight thermal insulation building material. The treatment and processing of graphite tailings are relatively complex, and traditional processing techniques cannot effectively incorporate them into building materials, especially in building materials that require high strength and high stability. The addition of graphite tailings may lead to uncertainty in product quality, and thus it is difficult to process in large quantities. The present invention adopts physical foaming technology to develop graphite tailings into high-performance lightweight thermal insulation building materials, and the obtained lightweight thermal insulation building materials have excellent thermal insulation performance, low density, high strength and good fire resistance. The present invention realizes the large-scale, green, efficient and high-quality disposal of graphite tailings, and the method of the present invention has low energy consumption.

[0020] The results of the embodiment show that the graphite tailings lightweight thermal insulation building material prepared by the present invention has a 28d strength of 4.3-11.8 MPa and a density of 780-1200 kg / m 3 , the thermal conductivity is 0.17~0.28W / (m·K). BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The present invention is a schematic diagram of the process of preparing lightweight thermal insulation building materials from graphite tailings according to an embodiment of the present invention. DETAILED DESCRIPTION

[0022] The present invention provides a method for preparing a lightweight thermal insulation building material of graphite tailings, comprising the following steps:

[0023] Mechanically foaming a nano foaming agent to obtain prefabricated foam; the nano foaming agent comprises the following components in percentage by weight: 0.1-1% alkyl glycoside, 0.1-1% nano bentonite, 0.05-1% cellulose reinforcing agent, and the balance water;

[0024] Mixing graphite tailings powder, cement, water and a water reducing agent to obtain a mixture;

[0025] mixing the mixed material with prefabricated foam to obtain concrete foam;

[0026] The concrete foam is sequentially molded and cured to obtain the graphite tailings lightweight thermal insulation building material.

[0027] Figure 1 This is a schematic diagram of the process of preparing lightweight thermal insulation building materials from graphite tailings according to an embodiment of the present invention. Figure 1 Provide detailed explanation.

[0028] In the present invention, unless otherwise specified, the raw materials involved are commercially available products well known in the art.

[0029] The invention conducts mechanical foaming on the nano foaming agent to obtain prefabricated foam.

[0030] In the present invention, the nano foaming agent comprises the following components in percentage by mass: 0.1-1% alkyl glycoside, 0.1-1% nano bentonite, 0.05-1% cellulose reinforcing agent, and the remainder of water. In the present invention, the mass percentage of alkyl glycoside in the nano foaming agent is preferably 0.3-0.5%, more preferably 0.3-0.4%; the alkyl glycoside is preferably decyl glucoside; the alkyl glycoside is used as a surfactant. In the present invention, the mass percentage of nano bentonite in the nano foaming agent is preferably 0.3-0.5%, more preferably 0.3-0.4%; the particle size of the nano bentonite is preferably 40-100nm, more preferably 50-80nm; the nano bentonite is used as a foam stabilizer. In the present invention, the mass percentage of the cellulose-based reinforcing agent in the nano foaming agent is preferably 0.3-0.5%, more preferably 0.3-0.4%; the cellulose-based reinforcing agent preferably includes cellulose and / or cellulose derivatives, and the cellulose derivatives preferably include hydroxypropyl methylcellulose; the relative molecular weight of the cellulose-based reinforcing agent is preferably 50,000-300,000, more preferably 100,000-200,000. The present invention has no special requirements for the preparation method of the nano foaming agent, and the components can be directly mixed evenly. In an embodiment of the present invention, the alkyl glycoside, nano bentonite and cellulose-based reinforcing agent are also referred to as foaming powder, and the nano foaming agent is also referred to as foaming liquid.

[0031] In the present invention, the mechanical foaming is preferably performed by a foaming machine; the air pressure of the mechanical foaming is preferably 0.3 to 3 MPa, and the density of the prefabricated foam is preferably 35 to 70 g / L.

[0032] The present invention adopts physical foaming, which is less affected by the external environment when treating graphite tailings, and can obtain products with qualified quality and stable performance; and the foaming agent used is a nano foaming agent, which has high stability, can reduce the bubble collapse phenomenon in the preparation process or the slurry stratification caused by foam rupture, and can also achieve early coagulation of the slurry, so that it has a higher strength at an early stage, thereby achieving efficient turnover of the product. Different from the chemical foaming method of foaming agents such as silicon carbide decomposing to generate carbon dioxide gas under high temperature environment, the present invention adopts the above-mentioned composite foaming agent to foam by physical friction, which is cleaner, low-carbon, and has better foaming quality.

[0033] The invention mixes graphite tailing powder, cement, water and a water reducing agent to obtain a mixture.

[0034] In the present invention, the mass content of graphite in the graphite tailings powder is usually 10-70%, and it also contains silicon dioxide (SiO2) 20-55wt%, aluminum oxide (Al2O3) 5-15wt%, iron oxide (Fe2O3) 1-10wt%, and calcium oxide (CaO) 1-5wt%; wherein, graphite is the main component in the graphite tailings powder, and its content usually depends on the efficiency of ore dressing; silicon dioxide mainly exists in the form of quartz, which is usually the main impurity component of the tailings; aluminum oxide mainly comes from aluminum silicate minerals. In the present invention, the particle size of the graphite tailings powder is preferably 160-200 meshes, and the graphite tailings powder is preferably obtained by crushing the graphite tailings with a hammer crusher (also referred to as broken in the embodiment), and then sieving. The present invention has no special requirements on the source of the graphite tailings, and the graphite tailings with a source familiar to those skilled in the art can be used.

[0035] In the present invention, the cement is preferably PO 42.5 cement. In the present invention, the mass ratio of the graphite tailing powder to cement is preferably 7:3 to 3:7, more preferably 7:3, 3:2 or 3:7. The present invention has no special requirements for the water. In the present invention, the ratio of the mass of the water to the total mass of cement and graphite tailing powder is preferably 0.2:1. In the present invention, the water reducer is preferably a polycarboxylate water reducer; the mass of the water reducer is preferably 0.1 to 0.3% of the total mass of graphite tailing powder and cement, more preferably 0.1 to 0.2%. The present invention uses a polycarboxylate water reducer to reduce the water-cement ratio, which can improve the strength and density of concrete.

[0036] In the present invention, the specific operation of mixing the graphite tailing powder, cement, water and water reducing agent is preferably: adding water to the mixer, then adding the water reducing agent for the first stirring and mixing, and then adding cement and graphite tailing powder for the second stirring and mixing. In the present invention, the speed of the first stirring and mixing is preferably 20r / min, and the stirring time is preferably 2min; the speed of the second stirring and mixing is preferably 50r / min, and the clockwise and counterclockwise stirring are respectively 2 to 5min. After the cement, graphite tailing powder, water and water reducing agent are mixed, a uniform slurry is obtained, that is, the mixture.

[0037] In the present invention, the fluidity of the mixture is preferably 240 to 250 mm.

[0038] After obtaining the mixed material and the prefabricated foam, the present invention mixes the mixed material and the prefabricated foam to obtain concrete foam.

[0039] In the present invention, the mass of the nano foaming agent in the prefabricated foam is preferably 6-16% of the total mass of the graphite tailing powder and cement in the mixture, and more preferably 7-8%.

[0040] In the present invention, the mixing of the mixture and the prefabricated foam is preferably carried out under stirring conditions, and the stirring rate is preferably 10r / min; the specific operation of mixing the mixture and the prefabricated foam is preferably: reducing the rotation speed of the mixer containing the mixture to 10r / min, injecting the prefabricated foam into the mixture, and stirring clockwise and counterclockwise for 1 to 2 minutes respectively, so that a uniform foam structure is formed in the concrete, that is, the concrete foam is obtained.

[0041] After obtaining the concrete foam, the present invention sequentially performs mold forming and curing on the concrete foam to obtain the graphite tailings lightweight thermal insulation building material. In the present invention, the mold forming preferably includes mold loading (i.e., pouring the concrete foam into a pre-prepared mold) and pre-curing, and the mold loading can also be vibrated, and the pre-curing is demolded; the pre-curing is preferably natural curing, and the time of the natural curing is preferably 0.5 to 2 days. The present invention forms the concrete into a material with a certain size and shape through the mold forming. In the present invention, the curing curing is preferably standard curing (i.e., standard curing), and the time of the standard curing is preferably 25 to 28 days. The present invention ensures that the material obtains sufficient strength and stability during the hardening process through the curing curing. In the present invention, when preparing blocks, the time of the natural curing is more preferably 12 hours, and after the natural curing, the wire cutting is performed to the desired size, and then the standard curing is performed, and the time of the standard curing is more preferably 27.5 days; when preparing thermal insulation wallboards, the time of the natural curing is more preferably 1 day, and the time of the standard curing is more preferably 27 days.

[0042] The process flow of preparing lightweight thermal insulation building materials from graphite tailings powder is simple and efficient, and can quickly achieve large-scale production. Compared with traditional graphite tailings treatment methods, it is more environmentally friendly, more energy-efficient, and higher quality.

[0043] The present invention provides a graphite tailings lightweight thermal insulation building material prepared by the preparation method described in the above technical solution.

[0044] In the present invention, the graphite tailings lightweight thermal insulation building material preferably includes building blocks or thermal insulation wall panels.

[0045] Graphite tailings usually present flaky or irregular particle morphology with fine particle size. This morphology may lead to poor uniformity in concrete and other building materials, affecting the overall performance of the material. Compared with traditional building materials (such as sand and gravel), the particle size distribution and morphology of graphite tailings are not ideal, which may affect the mechanical properties and stability of the mixed materials. In addition, the density of graphite tailings is usually low, which limits its application in building materials such as concrete. Low density may lead to a decrease in the strength and durability of concrete, thereby affecting the quality of the final product. In addition, graphite tailings have strong hydrophobicity, which will affect its binding with cement paste. In concrete, good adhesion is the key to ensure the strength and durability of the material. The hydrophobic properties of graphite tailings may cause the cement slurry to be unable to effectively wrap the tailings particles, thereby forming weaknesses and cracks. Although graphite is relatively stable under normal conditions, it may oxidize or degrade in extreme environments (such as high temperature, strong acid or strong alkali), which may become a potential problem in the long-term use of building materials, affecting the durability and safety of the materials. In addition: graphite tailings often contain other minerals (such as quartz, mica, etc.), the properties and characteristics of these minerals may interact with the properties of graphite, resulting in complex changes in material properties, for example, some paragenetic minerals may have high brittleness or chemical reactivity, affecting the application effect of graphite tailings in building materials. The mechanical properties of graphite tailings are generally not as good as traditional building materials, especially in terms of bearing capacity and compressive strength, which limits its application in load-bearing structures and makes it difficult to use it as the main building material. The treatment and processing of graphite tailings are relatively complex, and traditional processing techniques may not be able to effectively incorporate it into building materials, especially in building materials that require high strength and high stability. The addition of graphite tailings may lead to uncertainty in product quality. At present, the application of graphite tailings in the field of building materials still lacks relevant standards and specifications, which makes it uncertain in the development and application process, thereby reducing its acceptance in the field of building materials. The present invention realizes the large-scale disposal of graphite tailings, successfully obtains lightweight and high-strength thermal insulation materials with graphite tailings, and realizes the large-scale, green, efficient and high-quality disposal of graphite tailings. Compared with traditional building insulation materials, the graphite tailings lightweight insulation building material provided by the present invention has the following advantages:

[0046] Environmentally friendly and sustainable: The present invention utilizes the discarded graphite tailings, reduces the consumption of natural resources, and helps to reduce the pollution caused by waste to the environment;

[0047] Excellent thermal insulation performance: Building materials made of foam concrete have excellent thermal insulation performance, which can effectively insulate and improve the energy efficiency of buildings;

[0048] Low density and high strength: The building material provided by the present invention has a low density but sufficient strength to meet the requirements of the building structure and reduce the load of the building itself;

[0049] Good fire resistance: The building material provided by the present invention adopts foam concrete as the material, has good fire resistance, can effectively prevent the spread of fire, and improve the safety of the building.

[0050] In order to further illustrate the present invention, the graphite tailings lightweight thermal insulation building material and the preparation method thereof provided by the present invention are described in detail below in conjunction with examples, but they should not be construed as limiting the protection scope of the present invention.

[0051] The preparation process of the nano foaming agent used in the following examples is as follows:

[0052] Alkyl glucoside (decyl glucoside APG0810) is dissolved in water and stirred with a glass rod until it is dissolved to prepare an alkyl glucoside solution with a concentration of 0.4wt% (solution 1); nano bentonite (particle size 50-80nm) is dispersed in solution 1 and stirred with a glass rod until it is evenly dispersed, wherein the mass ratio of the nano bentonite to the alkyl glucoside is 1:1 (solution 2); hydroxypropyl methylcellulose (relative molecular weight 200000) is added to solution 2, wherein the amount of hydroxypropyl methylcellulose is 90wt% of the nano bentonite, and stirred with a glass rod until it is evenly dispersed, and the stirring speed is 20r / min to obtain a nano foaming agent.

[0053] Example 1

[0054] A graphite tailings lightweight thermal insulation building material (building block / thermal insulation wallboard) is prepared from the following materials: 560kg of PO 42.5 cement, 240kg of graphite tailings powder (160-200 meshes), 160kg of water, 1.5kg of polycarboxylic acid water reducer, and 64kg of nano foaming agent.

[0055] The preparation steps are as follows (process as Figure 1 shown):

[0056] (1) Weigh the required amount of water and add it into a blender.

[0057] (2) Weigh the required amount of polycarboxylate water reducer and pour it into a blender at a speed of 20 r / min for 2 min.

[0058] (3) Weigh the required cement and graphite tailings powder, pour them into a mixer, and stir at a speed of 50 r / min in a clockwise and counterclockwise direction for 2 to 5 minutes respectively until the slurry is uniform.

[0059] (4) The speed of the mixer was reduced to 10 r / min, and the nano foaming agent was foamed using a foaming machine (the foaming pressure was 0.6 MPa, and the density was 60 g / L), and then injected into the mixer, and stirred clockwise and counterclockwise for 1 to 2 min respectively.

[0060] (5) For foam insulation wall panels, simply inject the mixed slurry into the required mold, naturally cure for 1 day, remove the mold, and continue standard curing for 27 days; for lightweight blocks, simply inject the mixed slurry into the required mold, naturally cure for 12 hours, remove the mold, and then perform wire cutting to the required size. After cutting, continue standard curing for 27.5 days.

[0061] Graphite tailings lightweight blocks / insulation wall panels 28d (natural curing + standard curing) strength is 5.3 ~ 6.5MPa, density is 780 ~ 810kg / m 3 , the thermal conductivity is 0.17~0.21W / (m·K).

[0062] Example 2

[0063] A graphite tailings lightweight thermal insulation building material (building block / thermal insulation wallboard) is prepared from the following materials: 320 kg of PO 42.5 cement, 480 kg of graphite tailings powder (160-200 meshes), 160 kg of water, 1.5 kg of polycarboxylic acid water reducer, and 64 kg of nano foaming agent.

[0064] The preparation steps are the same as those in Example 1.

[0065] The 28d strength of graphite tailings lightweight blocks / insulation wall panels is 4.3-5.1MPa and the density is 900-980kg / m 3 , the thermal conductivity is 0.24~0.28W / (m·K).

[0066] Example 3

[0067] A graphite tailings lightweight thermal insulation building material (building block / thermal insulation wallboard) is prepared from the following materials: 320kg of PO 42.5 cement, 480kg of graphite tailings powder (160-200 meshes), 160kg of water, 1.5kg of polycarboxylic acid water reducer, and 58kg of nano foaming agent.

[0068] The preparation steps are the same as those in Example 1.

[0069] The 28d strength of graphite tailings lightweight blocks / insulation wall panels is 8.2-11.8MPa, and the density is 1050-1200kg / m 3 , the thermal conductivity is 0.24~0.28W / (m·K).

[0070] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a lightweight thermal insulation building material from graphite tailings, characterized in that: The following steps are involved: Mechanically foaming a nano foaming agent to obtain prefabricated foam; the nano foaming agent comprises the following components in percentage by weight: 0.1-1% alkyl glycoside, 0.1-1% nano bentonite, 0.05-1% cellulose reinforcing agent, and the balance water; Mixing graphite tailings powder, cement, water and a water reducing agent to obtain a mixture; mixing the mixed material with prefabricated foam to obtain concrete foam; The concrete foam is sequentially molded and cured to obtain the graphite tailings lightweight thermal insulation building material.

2. The preparation method according to claim 1, characterized in that: The air pressure of the mechanical foaming is 0.3-3 MPa, and the density of the prefabricated foam is 35-70 g / L.

3. The preparation method according to claim 1, characterized in that: The particle size of the graphite tailings powder is 160-200 meshes; and the cement is PO 42.5 cement.

4. The preparation method according to claim 1, characterized in that: The mass ratio of graphite tailing powder to cement is 7:3-3:7, the mass ratio of water to the total mass of cement and graphite tailing powder is 0.2:1, and the mass of the water reducer is 0.1-0.3% of the total mass of graphite tailing powder and cement.

5. The preparation method according to claim 1 or 4, characterized in that: The mass of the nano foaming agent in the prefabricated foam is 6-16% of the total mass of the graphite tailing powder and cement in the mixture.

6. The preparation method according to claim 1, characterized in that: The mixing of the mixed material and the prefabricated foam is carried out under stirring, and the stirring rate is 10 r / min.

7. The preparation method according to claim 1, characterized in that: The mold forming includes mold installation and pre-curing, and the mold is removed after the pre-curing; the pre-curing is natural curing, and the time of the natural curing is 0.5 to 2 days.

8. The preparation method according to claim 1, characterized in that: The curing process is standard curing, and the time of the standard curing is 25 to 28 days.

9. The graphite tailings lightweight thermal insulation building material prepared by the preparation method according to any one of claims 1 to 8.

10. The graphite tailings lightweight thermal insulation building material according to claim 9, characterized in that: The graphite tailings lightweight thermal insulation building material comprises building blocks or thermal insulation wall panels.

Citation Information

Cited By

  • All-solid-waste lightweight foam concrete thermal insulation material and preparation method thereof

    CN121573954A